The Impact of Operating Lease Capitalization on Financial Statements in Indonesia - Lisa Anggraini; Ayunita Ajengtiyas Saputri Mashuri; Husnah Nur Laela Ermaya (Jurnal Syntax Transformation, 2022)
PSAK 73 is a new accounting standard that introduces a single accounting model for lessees, namely recording their rental activities as capital leases. This study aims to determine the impact of operating lease capitalization on financial statements. This research is a type of quantitative research using secondary data in the form of annual reports and company financial statements. The object of this research is a company listed on the Indonesia Stock Exchange for the period 2018-2019 which discloses the value of future minimum lease payments on operating leases in the financial statements. Data analysis methods include descriptive statistical testing and Wilcoxon signed-rank test. The results show that operating lease capitalization has a significant effect on unrecorded lease liability, unrecorded lease assets, equity, and financial ratios. Also, empirical evidence shows that there are tax savings from operating lease capitalization